Influência do Sistema Colinérgico na sensibilização ao efeito estimulante do etanol - Takahashi, Shirley [UNIFESP] (2006)
Various neurotransmission systems have influence on the behavioral sensitization process developed after repeated administration of some drugs of abuse, among them the cholinergic system, which modulates the dopaminergic pathway’s functioning. In this study we evaluated the influence of scopolamine (an antagonist of cholinergic muscarinic receptors) on the development and _expression of behavioral sensitization to ethanol (Study I), as well as on the M1 binding, in animals classified as presenting high (AS) or low (BS) sensitization to ethanol (Study II). In Study I, four groups of male Swiss albino mice received one of the following during 21 days: saline+saline (sal/sal); 1.0 mg/kg of scopolamine+saline (escop/sal); salina+2.2 g/kg of ethanol (sal/2.2EtOH) or 1.0 mg/kg scopolamine+2.2 g/kg of ethanol (escop/2.2EtOH). Their locomotor activity was recorded during 20 minutes on the first, 7th, 14th and 21st days of treatment. Acutely, neither ethanol nor scopolamine altered their locomotor activity; however the co-administration of the both drugs induced a significant depressor effect to which tolerance was developed. Only the sal/2.2EtOH group developed sensitization. After the treatment, 3 challenge tests were carried out (on days 28th, 31st and 34th), in which half of the sal/sal group received saline and the other half received the challenge drug (ethanol in challenges 1 and 2 and scopolamine in challenge 3). In challenges 1 and 3 the animals were tested in activity cages and only the sal/2.2EtOH and escop/2.2EtOH groups expressed sensitization, suggesting there is cross-sensitization between ethanol and scopolamine. In challenge 2, which was conducted in a new environment (open-field arena), the _expression of the sensitization was blocked. In Study II, mice were treated during 21 days with saline or 2.2 g/kg ethanol (i.p.) and the ethanol treated mice were classified as AS or BS, according to their locomotor activity on day 21st. The animals were sacrificed and the bindings to M1 sites were examined by auto-radiographic analyses. No significant differences were found among groups (AS, BS and control) in any of the 20 brain regions analyzed. The present results suggest that scopolamine influences the process of sensitization to ethanol and that the cholinergic system participates in this process. However, the neuroadaptation that occurred after chronic ethanol treatment does not seem to change the binding to M1.